Thin Film Formation of Gallium Nitride Using Plasma-Sputter Deposition Technique - Flauta, R.; Kasuya, T.; Ohachi, T.; Wada, M. (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
The formation of gallium nitride (GaN) thin film using plasma-sputter deposition technique has been confirmed. The GaN film deposited on a glass substrate at an optimum plasma condition has shown x-ray diffraction (XRD) peaks at angles corresponding to that of (002) and (101) reflections of GaN. The remaining material on the sputtering target exhibited XRD reflections corresponding to that of bulk GaN powder. To improve the system’s base pressure, a new UHV compatible system is being developed to minimize the impurities in residual gases during deposition. The sputtering target configuration was altered to allow the monitoring of target temperature using a molybdenum (Mo) holder, which is more stable against Ga amalgam formation than stainless steel.